2010
DOI: 10.1017/s0021859610000523
|View full text |Cite
|
Sign up to set email alerts
|

Palatability,in situandin vitronutritive value of dried sainfoin (Onobrychis viciifolia)

Abstract: SUM M ARYThe current study was conducted to determine chemical composition, nutrient content and availability, metabolizable energy (ME) content and nutritive value of sainfoin hay for ruminants. Three ruminally cannulated Holstein cows were used for in situ and in vivo experiments, to determine rumen degradability and digestibility of sainfoin hay. Apparent total tract digestibility of nutrients was determined with feeding of sainfoin hay as the sole diet to achieve 10% more than maintenance energy requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…It has been shown by Parker and Moss (1981) that the voluntary intake of heifers was greater for sainfoin (CT level not defined) than for alfalfa. The same relationship was also reported for sheep fed fresh sainfoin (Karnezos et al, 1994) and sainfoin hay (CT 32.3 g kg −1 DM; Khalilvandi‐Behroozyar et al, 2010). Scharenberg et al (2007a) reported that sainfoin (CT ranging from 28–43 g kg −1 DM) was found to be more palatable than bird's‐foot trefoil ( Lotus corniculatus L.) (CT ranging from 8.7 to 20.3 g kg −1 DM) for sheep.…”
Section: Effects Of Condensed Tannins On Nutritive and Feeding Value supporting
confidence: 71%
“…It has been shown by Parker and Moss (1981) that the voluntary intake of heifers was greater for sainfoin (CT level not defined) than for alfalfa. The same relationship was also reported for sheep fed fresh sainfoin (Karnezos et al, 1994) and sainfoin hay (CT 32.3 g kg −1 DM; Khalilvandi‐Behroozyar et al, 2010). Scharenberg et al (2007a) reported that sainfoin (CT ranging from 28–43 g kg −1 DM) was found to be more palatable than bird's‐foot trefoil ( Lotus corniculatus L.) (CT ranging from 8.7 to 20.3 g kg −1 DM) for sheep.…”
Section: Effects Of Condensed Tannins On Nutritive and Feeding Value supporting
confidence: 71%
“…Another factor that may be involved is the content of condensed tannins in T‐SF, as these can act both directly on silage palatability and indirectly via a reduction in OM or NDF digestibility (Frutos et al ., ; Scharenberg et al ., ). However, beyond the fact that the tanniferous SF forage is recognized as highly acceptable to livestock (Khalilvandi‐Behroozyar et al ., ; Wang et al ., ), the CT content in T‐SF was moderate (1·14%) due to its dilution with the T grass, and lower than the range of concentrations associated with a decrease in feed intake (Waghorn et al ., ). Furthermore, the RC‐SF mixture that had a similar CT content was associated with one of the highest intakes.…”
Section: Discussionmentioning
confidence: 99%
“…The higher pH in the small intestine then weakens the bonds of CT‐containing protein, resulting in digestion and absorption of the amino acids. The protein‐binding capacity of CTs may also inhibit animal performance as not all the bypass protein bound to CTs is separated in the intestine, reducing availability to the animal (Khalilvandi‐Behroozyar, Dehghan‐Banadaky, & Rezayazdi, ; Min, Barry, Attwood, & McNabb, ; Osbourn, Terry, Cammell, & Outen, ). Further, although increased bypass protein is expected to decrease ammonia emissions from urine excretion, it also has been shown to decrease urea concentration in milk (Scharenberg et al., ), which may affect negatively animal productivity and thus negating overall system profitability.…”
Section: Environmental Impacts Of Sainfoin In Livestock Systemsmentioning
confidence: 99%